Host community perspectives on trainees participating in short‐term experiences in global health. Issue 11 (November 2016) - Kung, Tiffany H; Richardson, Eugene T; Mabud, Tarub S; Heaney, Catherine A; Jones, Evaleen; Evert, Jessica
Abstract : Context: High‐income country (HIC) trainees are undertaking global health experiences in low‐ and middle‐income country (LMIC) host communities in increasing numbers. Although the benefits for HIC trainees are well described, the benefits and drawbacks for LMIC host communities are not well captured. Objectives: This study evaluated the perspectives of supervising physicians and local programme coordinators from LMIC host communities who engaged with HIC trainees in the context of the latter's short‐term experiences in global health. Methods: Thirty‐five semi‐structured interviews were conducted with LMIC host community collaborators with a US‐based, non‐profit global health education organisation. Interviews took place in La Paz, Bolivia and New Delhi, India. Interview transcripts were assessed for recurrent themes using thematic analysis. Results: Benefits for hosts included improvements in job satisfaction, local prestige, global connectedness, local networks, leadership skills, resources and sense of efficacy within their communities. Host collaborators called for improvements in HIC trainee attitudes and behaviours, and asked that trainees not make promises they would not fulfil. Findings also provided evidence of a desire for parity between the opportunities afforded to US‐based staff and those available to LMIC‐based partners. Conclusions: This study provides important insights into the perspectives of LMIC host community members in the context of short‐term experiences in global health for HIC trainees. We hope to inform the behaviour of HIC trainees and institutions with regard to international partnerships and global health activities. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.